An Assessment of Forensic Accountants in Detection and Prevention of Financial Crimes in Business Organizations - Chukwuoyims Kevin Egwu Phd; DR. OWA FREDERICK (CNA); Osasona, Adedeji Viscker (Zien Journals, 2024)
The study was conducted to make an assessment of the role of forensic accountants in the detection and prevention of financial crimes in business organisations. The population of the study consisted of all members of staff of Champion Breweries Plc, Uyo, Akwa Ibom State. The study employed a survey design and selected seventy eight (78) respondents using a random sampling technique. We used a structured questionnaire to extract information from the respondents. The collected data were analysed using Pearson analysis. The data was then organised, tabulated, and analysed in frequency tables and percentages with the help of the statistical package for social sciences (SPSS) software. The study concluded that a proactive and well-equipped forensic accounting approach can act as a deterrent, discouraging potential wrongdoers and fostering a culture of financial responsibility. The integration of forensic accountants into the business sector's financial management framework is a vital step towards ensuring transparency, accountability, and the effective prevention of financial crimes. While it was recommended that relevant personnel undergo training programmes conducted by forensic accountants, this will empower them with the necessary skills to recognise and report suspicious financial activities, fostering a culture of transparency and accountability. Additionally, early adaptation of forensic accountants is crucial in detecting anomalies in financial records at an early stage.
Keywords: management; anomalies; transparency; stage